THE EFFECT OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, LOCUS OF CONTROL AND INCOME ON FINANCIAL MANAGEMENT BEHAVIOR ON THE MILLENNIAL GENERATION - Chintania Defa Pamella (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
The main purpose of this study is to examine the effect of financial literacy, financial attitudes, locus of control and income on financial management behavior in the millennial generation. The population of this research is the millennial generation, which is represented by active students majoring in Business Management, Accounting and Managerial Accounting Study Programs, employees class and regular class 2018 at the Batam State Polytechnic who have worked or had internships. The total respondents were 155 students. This study uses a quantitative approach and data collection methods through surveys by distributing questionnaires through google form. The results of this study are financial literacy, financial attitudes, locus of control and income have a significant positive effect on financial management behavior.